Peran Mediator Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Provinsi Sumatera Utara Dalam Penyelesaian Diskriminasi Dan Penelantaran Anak Akibat Perceraian Orangtua - Syarifuddin Syarifuddin; Ida Nadhirah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study was to determine the role of mediators in resolving parental conflicts which result in children becoming victims of discrimination and neglect as a result of divorce. This type of research is normative juridical through the approach of statutory regulations, as well as legal principles. The nature of this research is analytical descriptive, namely describing the problems that occur next, discussed and analyzed. Sources of data obtained from secondary data through government publications / websites and data collection tools are carried out through documents or data from the Office of Women's Empowerment and Child Protection of North Sumatra Province, the data analysis used is qualitative analysis. The role of the mediator is to prioritize the rights interests of the child over the interests of the parents. In the mediation process, the role of the mediator is as a formality for the parties to be able to proceed to the legal process in order to convict one of the parties. In addition, the mediator cannot force the parties to carry out or enforce the court's decision due to the parties' perception that the authority to execute court decisions including child custody lies in the court, and not in the Office of Women's Empowerment and Child Protection of North Sumatra Province. The mediator's efforts provide education to the parties that mediation is a tool in law enforcement in the police.